Pendidikan Nilai Perspektif Psikosufistik (Integrasi Psikologi dan Tasawuf dalam Mengembangkan Spiritualitas Pendidikan) - Muhammad Naufal Waliyuddin (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Abstract: If we think about the increasingly rapid development of science and technology in the present century, many studies have assessed that this is inversely proportional to the increase in moral, spiritual, and social ethical values which are more decadent. On that basis, not a few scholars have narrated the importance of value education with various variables. This paper examines further how the concept of value education in the Sufistic psychology (‘psychosufistical’) landscape—which is the result of the integration of psychology and sufism. The findings obtained are that the ‘psychosufistical perspective’ value education becomes a determinative foundation in fostering positive values that can make humans have character and quality based on the integration of psychology and Sufism as an esoteric dimension in Islam. The relationship between Living Values Education (LVE) and psychosufism in responding to the challenges of contemporary civilization can be formulated in several stages to achieve the goals of value education. Seven stages that can be implemented implicitly, namely: musyārathah, murāqabah, muhāsabah, mu’āqabah, mujāhadah mu’ātabah, and mukāsyafah. Then the method for optimizing the character of individuals and students specifically is to insert the three pillars of takhalli, tahalli, and tajalli into education. Thus the process of attaining spiritual intelligence—which obviously has an impact on social life—will have the potential to be developed.